Over-expressing ArabidopsisArabidopsis Myb transcription factors in Salvia stenophylla and sugarcane and development of micropropagation protocol for Salvia repens - Lekgari, Goitsemang Lorato Portia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.